Research progress of triangle counting in big data - Hongqiao JIN; Yihong DONG (Dianxin kexue)
Counting triangles in a graph is an important step to calculate the clustering coefficient and the transitivity ratio of the network，which is widely used in important role identification，spam detection，community discovery，biological detection etc.Counting triangles algorithm is mainly faced with two major problems of space-time consumption and accuracy.The representative algorithm of the counting triangles in the big graph was introduced.There existed two kinds of algorithms，which were exact counting algorithm and approximate counting algorithm.Exact counting algorithms were divided into internal memory algorithm，external memory algorithm and distributed algorithm.The space-time consumption or I/O consumption of exact counting algorithm was very large.Approximate counting algorithms were divided into auxiliary algorithm，static algorithm and streaming algorithm.In the end，the counting triangles algorithms were summarized.